2018
DOI: 10.1021/acs.energyfuels.8b00823
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Water Utility Lime Sludge for Flue Gas Desulfurization in Coal-Fired Power Plants: Part I. Supply–Demand Evaluation and Life Cycle Assessment

Abstract: The feasibility of lime-softening sludge utilization for flue gas desulfurization in coal-fired power plants was evaluated through a supply-demand analysis and a life cycle assessment (LCA). To evaluate the demand and supply of lime sludge to replace limestone on a national scale, the annual amount of lime sludge generated by water treatment utilities in the United States was estimated and compared with the annual amount of limestone used by coal-fired power utilities. To evaluate the environmental sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…Based on the results presented in Part I of this article, the reuse of lime sludge generated at water utilities to capture acid gases at power utilities can be a sustainable and cost-effective solution benefiting both the water and energy sectors. 1 The laboratory-scale results presented in this work confirmed the high reactivity of various tested lime sludge samples without negatively affecting mercury reemission or undesirable elements leaching into the scrubber slurry. More testing at a pilot scale is needed to further evaluate possible operational issues before consideration for potential large-scale implementation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Based on the results presented in Part I of this article, the reuse of lime sludge generated at water utilities to capture acid gases at power utilities can be a sustainable and cost-effective solution benefiting both the water and energy sectors. 1 The laboratory-scale results presented in this work confirmed the high reactivity of various tested lime sludge samples without negatively affecting mercury reemission or undesirable elements leaching into the scrubber slurry. More testing at a pilot scale is needed to further evaluate possible operational issues before consideration for potential large-scale implementation.…”
Section: Discussionsupporting
confidence: 73%
“…Overall, lime sludge can be used as a potential replacement to limestone for the removal of acid gases from power plant flue gas. On the basis of the results presented in Part I of this article, the reuse of lime sludge generated at water utilities to capture acid gases at power utilities can be a sustainable and cost-effective solution benefiting both the water and energy sectors . The laboratory-scale results presented in this work confirmed the high reactivity of various tested lime sludge samples without negatively affecting mercury re-emission or undesirable elements leaching into the scrubber slurry.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Wet scrubbers are widely used for removal of SO 2 from flue gas through reaction with limestone slurries . A supply–demand evaluation and a life cycle assessment performed in Part I of this investigation demonstrated that switching from limestone to lime-softening sludge can be highly beneficial to water treatment and power generation industries, both economically and environmentally …”
Section: Introductionmentioning
confidence: 89%
“…1 A supply−demand evaluation and a life cycle assessment performed in Part I of this investigation demonstrated that switching from limestone to lime-softening sludge can be highly beneficial to water treatment and power generation industries, both economically and environmentally. 2 In Part II of this work, the feasibility of lime sludge utilization in the flue gas desulfurization (FGD) process was evaluated by conducting laboratory-scale tests with a simulated flue gas at a flow rate of 0.5 L/min (LPM). 3 Eight lime sludge samples and a baseline limestone sample were evaluated for their performance capability to remove SO 2 from a simulated flue gas, while monitoring Hg re-emission from the scrubber.…”
Section: Introductionmentioning
confidence: 99%